Модель бізнесу українських банків в залученні коштів клієнтів - Панасенко, Г.О.; Бортніков, Г.П. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The choice of business model significantly affects different set of factors, including the regulation of banks, the level of competition in the market, the image of a particular institution, variability balances on customer accounts. A significant reduction of the network may signal the approach of disaster or owners of the bank decision to withdraw from the market. The structure of the resource base to determine the criteria for clustering of banks, particularly in terms of depending on customer accounts. pay depositors for deposit guarantee scheme. We consider the resource potential of the bank in terms of customer funds from two points of view - from the perspective of demand and supply position resources.